Public Information Disclosure as a Reflection of Administrative Governance: A Content Analysis of the Official Websites of Ministry of Health's Vertical Hospitals Based on Law No. 14 of 2008 - Inna Noor Inayati (CV. Get Press Indonesia, 2025)
This study investigates the level of Public Information Disclosure (PID) on the official websites of the Ministry of Health's Vertical Hospitals (RSVKs) as a direct reflection of their adherence to Good Administrative Governance (GAG) principles, as mandated by Indonesian Law No. 14 of 2008. PID is theoretically critical for public accountability and preventing institutional misuse of authority (Cahyono & Haryadi, 2023; Amane et al., 2025). Objective: The research aimed to quantitatively measure the proactive disclosure compliance of RSVKs. Methods: A Systematic Quantitative Content Analysis was employed, utilizing a specialized Digital Information Disclosure Index (DIDI) and a binary coding scheme (N=40 mandatory items) to analyze the digital content of all RSVK websites in October 2025. Inter-coder reliability was ensured using Cohen’s Kappa ( 0.80) (Krippendorff, 2019). Results: The overall digital compliance level was Moderate, with a mean DIDI score of μ= 65.4% SD = 10.8%). A significant disparity was found between compliance with Fiscal Accountability (Periodic Disclosure:μ=75.1%) and Procedural Responsiveness (Anytime Disclosure: = 55.7%), particularly concerning Procurement Data for Goods & Services (40%). Qualitative analysis highlighted technical barriers, including the pervasive use of non-searchable PDF formats and poor placement (Norris & Lloyd, 2020). Conclusion: RSVKs demonstrate a model of formalistic transparency (compliance of form) driven by top-down requirements, failing to achieve substantive transparency due to institutional risk-aversion and managerial constraints. Implication: The study recommends that the Ministry of Health issue regulations mandating the publication of all required documents in searchable digital formats and implement transparency-focused HR reforms (Wulandari, 2025) to transition from defensive administrative compliance to a genuine GAG commitment.